2004
DOI: 10.2307/1543206
|View full text |Cite
|
Sign up to set email alerts
|

Histidine Suppresses Zinc Modulation of Connexin Hemichannels

Abstract: Zinc has been shown to modulate hemichannel currents of connexins Cx35 and Cx38 in Xenopus oocytes (1).In both cases the effects were biphasic; i.e., low concentrations of zinc enhanced, whereas higher concentrations decreased, the magnitudes of the voltage-activated hemichannel currents. The present study was designed to determine the effects of zinc on hemichannels formed by Cx26, a connexin reportedly expressed on dendrites of carp horizontal cells and implicated in a mechanism for photoreceptor feedback (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Our pH data are in general agreement with Ripps et al (17), but for Zn 2ϩ , we observed a higher sensitivity and a monophasic rather than a biphasic response, as reported by Chappell et al (34). We have no explicit explanation for these differences, although the experimental protocols used by Chappell et al (34) that stepped the membrane potential positive could progressively activate Cx26 hemichannels, which exhibit slow kinetics, thereby giving the appearance of a biphasic response with activation counteracting inhibition at low Zn 2ϩ concentrations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our pH data are in general agreement with Ripps et al (17), but for Zn 2ϩ , we observed a higher sensitivity and a monophasic rather than a biphasic response, as reported by Chappell et al (34). We have no explicit explanation for these differences, although the experimental protocols used by Chappell et al (34) that stepped the membrane potential positive could progressively activate Cx26 hemichannels, which exhibit slow kinetics, thereby giving the appearance of a biphasic response with activation counteracting inhibition at low Zn 2ϩ concentrations.…”
Section: Discussionsupporting
confidence: 93%
“…Both pH and Zn 2ϩ had been shown to inhibit Cx26 hemichannel currents expressed in Xenopus oocytes (17,34). Our pH data are in general agreement with Ripps et al (17), but for Zn 2ϩ , we observed a higher sensitivity and a monophasic rather than a biphasic response, as reported by Chappell et al (34).…”
Section: Discussionsupporting
confidence: 92%
“…Although most hemichannels appear to be closed when Ca 2+ is above 1 mmol/L, this mechanism may be of pathophysiological significance, for example, during cerebral ischemia, where the extracellular Ca 2+ level may be as low as 0.1 mmol/L (251). The extracellular levels of other divalent cations like Zn 2+ , Cd 2+ , Co 2+ , Ba 2+ , and Mg 2+ also affects the gating properties, with the general picture being inhibition with increasing concentrations (85, 86, 160, 668). Replacing extracellular Na + by K + , Cs + , or Rb + causes an increase in the open probability of Cx46 and Cx50 hemichannels, suggesting that monovalent cations may interact with Ca 2+ in determining the activity of hemichannels (653).…”
Section: Noncoupling Roles Of Connexinsmentioning
confidence: 99%
“…Cx HCs are not only regulated by extracellular Ca 2+ , but also by other divalent cations, including Zn 2+ , as well as pH (Ebihara and Steiner, 1993 ; Trexler et al, 1999 ; Chappell et al, 2004 ; Ripps et al, 2004 ). For Cx26 HCs, sensitivity to pH falls in a physiological range such that substantial inhibition occurs at normal plasma pH levels of ~7.4.…”
Section: Other Potential Hc Regulators In Kid Syndromementioning
confidence: 99%